2004
DOI: 10.1364/ol.29.002348
|View full text |Cite
|
Sign up to set email alerts
|

Mixed data rate and format transmission (40-Gbit/s non-return-to-zero, 40-Gbit/s duobinary, and 10-Gbit/s non-return-to-zero) by mid-link spectral inversion

Abstract: A polarization-diverse subsystem based on periodically poled lithium niobate waveguides is used as an optical phase conjugator for compensation for linear and nonlinear distortion. We show successful transmission formats of 13 x 40 Gbit/s non-return-to-zero mixed with 6 x 10 Gbit/s non-return-to-zero and 40-Gbit/s duobinary over 8 x 100 km of standard single-mode fiber. A single phase conjugator is used to conjugate all data formats, including the alternative duobinary format, simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…These waveguides can be operated at significantly lower temperatures. In several recent transmission experiments APE [4]- [7], [25], [26] and MgO-doped [27]- [32] PPLN waveguides are employed operating at temperatures ranging from 50…”
Section: A Ppln Waveguide For Opcmentioning
confidence: 99%
See 3 more Smart Citations
“…These waveguides can be operated at significantly lower temperatures. In several recent transmission experiments APE [4]- [7], [25], [26] and MgO-doped [27]- [32] PPLN waveguides are employed operating at temperatures ranging from 50…”
Section: A Ppln Waveguide For Opcmentioning
confidence: 99%
“…As a result, a difference in residual dispersion is present after transmission. In most OPC-based transmission experiments reported so far, the difference in residual dispersion is compensated for by optimizing the postcompensation after transmission on a per channel basis [15], [16], [25], [27]- [32], [39], [40]. Alternatively, the third-order dispersion can be compensated for using a slope compensator [38].…”
Section: A Theory Of Phase Conjugationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been experimentally shown that OPC can compensate for chromatic dispersion [11]- [15], self-phase modulation (SPM), [16] and also intrachannel nonlinear impairments [17]- [19]. The key advantages of OPC are that simultaneous processing of multiple channels is possible [20] and that an OPC is transparent to modulation format and data rate [21].…”
Section: Introductionmentioning
confidence: 99%